Blockade of Wnt/β-Catenin Pathway Aggravated Silica-Induced Lung Inflammation through Tregs Regulation on Th Immune Responses - Wujing Dai; Fangwei Liu; Chao Li; Yiping Lu; Xiaowei Lu; Sitong Du; Ying Chen; Dong Weng; Jie Chen (Mediators of Inflammation)
CD4+ T cells play an important role in regulating silica-induced inflammation and fibrosis. Recent studies showed that Wnt/β-catenin pathway could modulate the function and the differentiation of CD4+ T cells. Therefore, Wnt/β-catenin pathway may participate in the development and progress of silicosis. To investigate the role of Wnt/β-catenin pathway, we used lentivirus expressing β-catenin shRNA to block the Wnt/β-catenin pathway by intratracheal instillation to the mice model of silicosis. Treatment of lentivirus could significantly aggravate the silica-induced lung inflammation and attenuated the fibrosis at the late stage. By analyzing CD4+ T cells, we found that blockade of Wnt/β-catenin pathway suppressed regulatory T cells (Tregs). Reciprocally, enhanced Th17 response was responsible for the further accumulation of neutrophils and production of proinflammatory cytokines. In addition, blockade of Wnt/β-catenin pathway delayed the Th1/Th2 polarization by inhibiting Tregs and Th2 response. These results indicated that Wnt/β-catenin pathway could regulate Tregs to modulate Th immune response, which finally altered the pathological character of silicosis. Our study suggested that Wnt/β-catenin pathway might be a potential target to treat the silica-induced inflammation and fibrosis.